2011
DOI: 10.4314/wajm.v29i6.68299
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Simultaneous Fracture of the Carpal Scaphoid Successfully Treated with Conservative Cast Immobilisation: A Case Report

Abstract: BACKGROUND: The scaphoid is the most prominent of the carpal bones in the first row and the most frequently fractured of all the carpal bones. Bilateral simultaneous scaphoid fractures are uncommon. OBJECTIVE: To report bilateral simultaneous fractures of the carpal scaphoid bones and their successful treatment with bilateral thumb spacia casts METHODS: A 28-year-old medical practitioner presented with a day history of painful swollen wrists following a fall on both outstretched hands. He was fully examined an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In a study by Terkelsen and Jepsen, the incidence of non-union was not found to be greater in patients with a removable short-arm plaster cast than in patients treated with a long-arm thumb plaster cast [13] . In contrast, Gellman et al reported that in patients to whom a long-arm thumb plaster cast was applied for 6 weeks from the beginning, union time was 3 months early [14] Kaneshiro et al showed a change of place of more than 3 mm of fracture fragments during pronation and supination in forearm short-arm thumb plaster casting in an experimental study where scaphoid fractures were created [15] . Long-arm thumb plaster casting was used for the case presented here.…”
Section: Discussionmentioning
confidence: 97%
“…In a study by Terkelsen and Jepsen, the incidence of non-union was not found to be greater in patients with a removable short-arm plaster cast than in patients treated with a long-arm thumb plaster cast [13] . In contrast, Gellman et al reported that in patients to whom a long-arm thumb plaster cast was applied for 6 weeks from the beginning, union time was 3 months early [14] Kaneshiro et al showed a change of place of more than 3 mm of fracture fragments during pronation and supination in forearm short-arm thumb plaster casting in an experimental study where scaphoid fractures were created [15] . Long-arm thumb plaster casting was used for the case presented here.…”
Section: Discussionmentioning
confidence: 97%
“…Fractures exhibiting discordance bilaterally based on Herbert's classification were documented in 25% of cases (n = 4). In one case (n = 1; 6.25%), a B2 fracture on the right and a B3 fracture on the left were reported [15]. In another case, an A2 fracture on the right and a B1 fracture on the left were observed [24].…”
Section: Fracture Sitementioning
confidence: 95%
“…In 75% of the cases (n = 12), the injury mechanism involved high-energy trauma. Specifically, 37.5% of the cases (n = 6) resulted from falls from a height [11][12][13][14]20,23], 6.25% (n = 1) were related to a traffic accident [24], 18.75% (n = 3) were associated with falls onto both outstretched hands [15,16,19], and 12.5% (n = 2) were attributed to sports-related trauma (Table 2) [1,21]. Four patients (n = 4; 25%) did not disclose specific traumatic events; instead, they reported multiple minor traumas occurring repeatedly over time, categorizing these fractures as stress fractures [17,18,22,25].…”
Section: Mechanism Of Injurymentioning
confidence: 99%